2015
DOI: 10.3221/igf-esis.35.29
|View full text |Cite
|
Sign up to set email alerts
|

Crack path in liquid metal embrittlement: experiments with steels and modeling

Abstract: We review the recent experimental clarification of the fracture path in Liquid Metal Embrittlement with austenitic and martensitic steels. Using state of the art characterization tools (Focused Ion Beam and Transmission Electron Microscopy) a clear understanding of crack path is emerging for these systems where a classical fractographic analysis fails to provide useful information. The main finding is that most of the cracking process takes place at grain boundaries, lath or mechanical twin boundaries while cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Moreover, it has been shown that oxygen in the liquid LBE can drive the Pb atoms to enter the lattice along the channels formed in the cracked oxide [24]. Brittle fracture initiates and propagates along all types of interfaces such as lath interfaces, block interfaces, packet interfaces and martensitic grain boundaries in agreement with the findings of Auger et al [25]. Brittle fracture propagation through lath or packet is not excluded but due to the size of these microstructural items, it is difficult to decide.…”
Section: Fig 10supporting
confidence: 81%
“…Moreover, it has been shown that oxygen in the liquid LBE can drive the Pb atoms to enter the lattice along the channels formed in the cracked oxide [24]. Brittle fracture initiates and propagates along all types of interfaces such as lath interfaces, block interfaces, packet interfaces and martensitic grain boundaries in agreement with the findings of Auger et al [25]. Brittle fracture propagation through lath or packet is not excluded but due to the size of these microstructural items, it is difficult to decide.…”
Section: Fig 10supporting
confidence: 81%
“…( 8) to the ground truth values produced by the Eq. (7). To this end the two functions are plotted and the surface plots are presented in Fig.…”
Section: Symbolic Regressionmentioning
confidence: 99%
“…Interface controlled fracture is an important phenomenon present in many structural alloys such as Al-Li [1,2], β-Titanium alloys [3], multi-phase steels [4] and ceramics [5][6][7]. Similarly, when exposed to aggressive chemical agents (e.g.…”
Section: Introductionmentioning
confidence: 99%